PENGARUH METODE PEMBELAJARAN SISWA MEMPUNYAI PERTANYAAN DALAM MENINGKATKAN KEMAMPUAN MENULIS BERITA OLEH SISWA KELAS X SMA PRAYATNA MEDAN TAHUN PEMBELAJARAN 2012/2013 - Siti Sri Rahayu (Asas: Jurnal Sastra, 2012)
The research was motivated by the persistence of students who havedifficulties in writing a news story, include difficulty putting the elements ofnews, keruntutan exposure, use short sentences and clear, kemenarikkantitles, as well as the correct use of spelling in the news that are customizedby EYD (spelling in polishing) ukan. The difficulty arises due to lack ofstudent interest and no innovation in the learning process. This indicates thatthe learning news writing achievement indicators do not meet the learningobjectives. Therefore, the researchers tested the method intended to questionstudent have in learning to write news.The method used in this study is quasi-experimental method with the onegroup pretest-posttest single group design performed on members of thepopulation, namely the class X High School Private Prayatna field with thesample X1 grade 30 students as a class experiment. In this research, theexperimental class were given the news writing skills test before and afterusing this method have student question. The results of the calculation ofvariance test group studied sample count obtained F = 1.50 and F table =1.68. Price Fhitung <F table is 1.50 <1.68. It proves that the variance of thepopulation is homogeneous. Calculation results obtained t0 t test outweighthe TTable 9.69> 2.04 at the 5% significance level and the calculation of nilhypothesis testing (H0) is rejected and the alternative hypothesis (Ha) isaccepted. This proves that the method of student question have a positiveinfluence high school students of class X Prayatna Field Learning Year2012/2013.Keywords: Effect of method of question student have in learning to writenews